Mental health of Ukrainian children and youth during the Russian-Ukrainian war: a scoping review - Silwal, Sanju; Minja Westerlund, Minja; Osokina, Olga; Ivnyev, Boris; Ahramo, Kaisa; Ortin Peralta, Ana; Sourander, Andre (United Kingdom, 2026)
Introduction: On 24 February 2022, Russia launched a full-scale invasion of Ukraine, escalating the conflict that began in April 2014 with the invasion and occupation of parts of Eastern Ukraine and Crimea by Russian forces. We conducted a scoping review of studies examining mental health problems of children and youth from the beginning of the war in 2014 until 2024. Additionally, we examined traumatic events, resilience, risk and protective factors of mental health.
Methods: We searched PubMed and PsycINFO for articles published in English and Open Ukrainian Citation Index and Ukrainian Scientific Periodical for articles published in Ukrainian. We reviewed quantitative and qualitative articles, focusing on children and adolescents aged 0-19 years. The review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) and the protocol was registered with the Open Science Framework.
Results: 37 articles (20 English, 17 Ukrainian) met the inclusion criteria. Most studies were cross-sectional in design or quantitative and focused on children and youth residing in Ukraine. The mental health outcomes were diverse, with prevalence rates varying across studies. Among the included studies on mental health, few studies assessed resilience among war-exposed adolescents. Forced displacement, exposure to war-related events and separation from parents were associated with mental health problems. Protective factors included perceived social support, living in a familiar environment and problem-focused coping skills.
Conclusion: Methodologically comparable studies, including prospective and mixed-methods studies, are needed to further advance our understanding of the long-term psychological effects of war and explore their perceptions and experiences of wartime adversities.
Protocol registration: Open Science Framework (https://osf.io/cuhgd/).